2000
DOI: 10.1007/bf02256972
|View full text |Cite
|
Sign up to set email alerts
|

Properties of 2,3-dihydro-imidazolo[1,2-a]pyridines. (Review)

Abstract: From our previous review [1], in which we discussed the synthcsis, structure, tautomerism, and nomenclature of 2,3-dihydroimidazo[l,2-a]pyridines, it tbllows that compounds of type A-C have wide-ranging practical applications.Data on the chemical properties of 2-oxoimidazopyridincs B, which have amphoteric characteristics and tbrm watcr-solublc salts with mineral acids and alkalies, wcrc studied in detail and analyzed in [2]. They wetc used to obtain many dycs [3][4][5], which were also synthesized [6] from 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
3
0
1
Order By: Relevance
“…2005, 48, chemists to pursue the synthesis of numerous imidazopyridine derivatives 6 and study their properties. 7 Synthetic approaches include reaction of aminopyridines with R-functionalized and R,β-unsaturated carbonyl compounds, 1,3-dicarbonyl compounds, vicinal diols as well as with simple aldehydes and ketones, often in a multicomponent reaction. 8À10 Reactions involving Sandmeyer conditions, rearrangement, cycloaddition, Michael addition and other miscellaneous ones were also employed for the synthesis of imidazopyridines.…”
mentioning
confidence: 99%
“…2005, 48, chemists to pursue the synthesis of numerous imidazopyridine derivatives 6 and study their properties. 7 Synthetic approaches include reaction of aminopyridines with R-functionalized and R,β-unsaturated carbonyl compounds, 1,3-dicarbonyl compounds, vicinal diols as well as with simple aldehydes and ketones, often in a multicomponent reaction. 8À10 Reactions involving Sandmeyer conditions, rearrangement, cycloaddition, Michael addition and other miscellaneous ones were also employed for the synthesis of imidazopyridines.…”
mentioning
confidence: 99%
“…Substituted fused heterocycles can be found in many types of synthetic and naturally occurring medicinal substances such as coelenterazine, an imidazolopyrazinone derivative . It was found that imidazo[1,2- a ]pyrazinones exhibit a significant solvatochromism and bio- and chemiluminescence. , Imidazo[1,5- a ]pyridines possess various applications such as dyes, optical data carriers, pesticides, fungicides, hypoglycemic agents, and compounds exhibiting antitumor, anti-inflammatory, antipyretic, and analgesic activity . Oxidative condensation–cyclization of aldehydes with 2-aminomethylpyridines or Pictet–Spengler strategy are among the most important routes to synthesize of these types of fused heterocycles …”
Section: Synthesis Of Five-membered Heterocyclesmentioning
confidence: 99%
“…130 °C) under a nitrogen atmosphere for 18 h did produce a quaternary ammonium heterocycle, but not 4 . Rather, this N , N -dialkylation produced imidazopyridinium bromide 7a − c ( m = 1) as the sole product. Intrigued by this transformation and the fact that imidazopyridium salts are reported to have hypoglycemic, type I allergy, and neuromuscular blocking properties, we decided to further investigate the synthesis and hydrolysis reactions of these imidazopyridium salts.…”
mentioning
confidence: 98%